Factors that drives the determinant of commercial property value; Professional’s perspective - Atan, Aina Mardia; eni, sabariah; Omar, Abdul Jalil; Fazian Hashim (Research in Management of Technology and Business, 2021)
Abstract The stipulation for commercial property in the Malaysia property market has shown notable growth and potentially gives a major impact to global property portfolios. The objective of this research is to identify the sets of commercial property value attributes in the context of Malaysia property market and to analyses valuers’ professional perspective on the level of significance for each commercial property value attributes in determining commercial property value in Malaysia. This research is needed as it will inform existing and prospective real estate stakeholders, investors, and including facility managers of the major determinants in valuing their commercial property investments. Secondly, the determinants will be a tool for valuers and researchers in determining property value. Qualitative and quantitative methodology is adopted where a set of determinant were generated from previous literature studies on the factors that influence commercial property value. The determinants are then distributed through surveys to Registered Valuers and professionals’ in the real estate fields’ in Malaysia to confirm the variables taken to value commercial property. The data has been analyzed using the Statistical Package of the Social Sciences (SPSS) 25.0 software to rank the attributes in establishing their mean scores (MS) and to conduct the reliability test (Cronbach’s Alpha) of the data collected in SPSS to find the COV. The outcome from this research were to determine the main determinants adopted by Registered Valuers in Malaysia in determining commercial property value.